Giant placental chorioangioma with favorable outcome: a case report and literature review of literature - Caldas, R T M; Peixoto, A B; Paschoini, M C; Adad, S J; Souza, M L R; Araujo Júnior, E (Ceska gynekologie, 2015)
OBJECTIVE: To describe a case of prenatal diagnosis of a giant placental chorioangioma with favorable outcome. DESIGN: A case report. SETTING: Gynecology and Obstetrics Service, Federal University of Triângulo Mineiro (UFTM), Uberaba-MG, Brazil. CASE REPORT: The placental chorioangioma is the most common benign tumor, but the type giant has a small prevalence, ranging from 1:16.000 to 1:50.000 pregnancies. We reported a case of a patient aged 18, pregnant for the first time, who performed a routine obstetric ultrasound was found to have polyhydramnios associated with placental vascular lesions suggestive of chorioangioma also was defined by fetal magnetic resonance imaging and confirmed by pathological examination.
Keywords: Hemangioma; Pregnancy Complications, Neoplastic; hemangiom; Adolescent; placental; Pregnancy; pregnancy; těhotenství; magnetic resonance imaging.; nemoci placenty; Diagnosis, Differential; Ultrasonography, Prenatal; ultrasonografie prenatální; mladiství; novorozenec; Placenta Diseases; ultrasound; lidé; ženské pohlaví; Humans; Infant, Newborn; diferenciální diagnóza; chorioangioma; Female; nádorové komplikace v těhotenství